2015
DOI: 10.1097/inf.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the US Two-dose Varicella Vaccination Program on the Epidemiology of Varicella Outbreaks

Abstract: Background A routine 2-dose varicella vaccination program was adopted in 2007 in the United States to help further decrease varicella disease and prevent varicella outbreaks. We describe trends and characteristics of varicella outbreaks reported to CDC during 2005–2012 from 9 states. Methods Data on varicella outbreaks collected by 9 state health departments were submitted to CDC using the CDC outbreak reporting worksheet. Information was collected on dates of the outbreak, outbreak setting, and number of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
(19 reference statements)
0
23
1
Order By: Relevance
“…This study found that the proportion of BV cases among all outbreak-related cases was 56.5%, higher than the results of a population-based survey (22%) (Chaves et al, 2008), but within the range of several outbreak-based studies (42-76%) (Leung et al, 2015;Zhang et al, 2014b;Zhu et al, 2017). It was also found that the proportion of BV cases showed an increasing trend from 30.4% in 2008 to 85.7% in 2017.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…This study found that the proportion of BV cases among all outbreak-related cases was 56.5%, higher than the results of a population-based survey (22%) (Chaves et al, 2008), but within the range of several outbreak-based studies (42-76%) (Leung et al, 2015;Zhang et al, 2014b;Zhu et al, 2017). It was also found that the proportion of BV cases showed an increasing trend from 30.4% in 2008 to 85.7% in 2017.…”
Section: Discussioncontrasting
confidence: 41%
“…The results of a meta-analysis also showed that VE against all varicella increased significantly from 81% in the single-dose VarV era to 92% in the two-dose VarV era (Marin et al, 2016). In addition, monitoring data showed that the numbers, size, and duration of varicella outbreaks in the USA have decreased significantly since the implementation of a routine two-dose VarV program (Leung et al, 2015). Fortunately, a voluntary two-dose VarV schedule has been recommended in Shanghai, China, since November of 2017 (Shanghai Municipal Health and Family Planning Commission, 2017) and was included in the immunization program of Shanghai in August 2018 ( Figure 1).…”
Section: Discussionmentioning
confidence: 97%
“…20 Study on epidemiology of varicella during the 2-dose VarV Program in the United States shows that between the period 2005-2006 (before the 2-dose recommendation) and 2013-2014, overall varicella incidence declined 84.6%, with the largest declines reported in children aged 5-9 years (89.3%) and 10-14 years (84.8%). 21 The routine 2-dose varicella vaccination program appears to have significantly reduced the number, size and duration of varicella outbreaks in the US 22 A 2nd dose may deserve additional consideration to control varicella outbreak and for development of an adequate and persisting antibody response. 23 In conclusion, in order to prevent varicella transmission and outbreaks, 2 doses of secondary VarV immunization are preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have documented significant declines in varicella incidence in the United States since the varicella vaccination program was implemented in 1996 through the early years of the 2-dose program (1,(3)(4)(5)(6)(7)(8). During 1995-2010, data to assess impact of the varicella vaccination program were obtained from a varicella active surveillance project, which was discontinued in 2010 (3).…”
Section: Discussionmentioning
confidence: 99%